Risk Culture and COVID-19 Protective Behaviors: A Cross-Sectional Survey of Residents in China - Bi, Xuejing; Zhang, Qiao; Fan, Kaisheng; Tang, SiYu; Guan, HanWen; Gao, XueQin; Cui, Yu; Ma, Yi; Wu, QunHong; Hao, YanHua; Ning, Ning; Liu, Chaojie (Frontiers in Public Health, 2021)
The COVID-19 outbreak caused by the Severe Acute Respiratory Syndrome CoronaVirus type 2 (SARS-CoV-2) has spread across the world. However, our understanding of the public responses, in particular in adopting protective behaviors, has been limited. The current study aimed to determine the level of protective behaviors adopted by the residents in China and its association with their cultural attributes. A national cross-sectional online survey was conducted in mainland China from 4th to 13th August 2020. Protective behaviors were assessed as a summed score (ranging from 0 to 40) measured by ten items. The self-report tendency of study participants toward the four cultural attributes (individualism, egalitarianism, fatalism, hierarchy) was rated on a seven-point Likert scale. A total of 17651 respondents returned a valid questionnaire, representing 47.9% of those who accessed the online survey. Most (89.8%) respondents aged between 18 and 45 years in the age range of and 47.7% were male. High levels of protective behaviors (34.04 ± 5.78) were reported. The respondents had high scores in the cultural attributes of hierarchy (Median = 5) and egalitarianism (Median = 5), compared with low scores in individualism (Median = 1) and fatalism (Median = 1). High levels of protective behaviors were associated a higher tendency toward egalitarianism (AOR = 2.90, 95% CI 2.67–3.15) and hierarchy (AOR = 1.66, 95% CI 1.53–1.81) and a low tendency toward fatalism (AOR = 1.79, 95% CI 1.63–1.97) and individualism (AOR = 2.62, 95% CI 2.41–2.85). The cultural attributes explained 17.3% of the variations in the protective behavioral scores. In conclusion, the adoption of protective behaviors is associated a risk culture characterized by high levels of hierarchy and egalitarianism and low levels of individualism and fatalism. Government actions and communication strategies need to adapt to the cultural characteristics of their target audience.